Multicenter study for defining the breakpoint for rifampin resistance in Neisseria meningitidis by rpoB sequencing - Taha, Muhamed-Kheir (2010)
Fil: Taha, Muhamed-Kheir. National Reference Centre for Meningococci. Institut Pasteur; Francia.